La Tolleranza Glicidica Nell'insufficienza Renale Cronica - A.M. Ciciani; F. Bergesio; G. Monzani; R. Ciuti; F. Martinelli; R. Piperno; G. Baldereschi; M. Salvadori (AboutScience Srl, 1997)
Abstract non disponibile